Tanggung Jawab Pejabat Pembuat Akta Atas Keabsahan Akta Peralihan Saham yang Dibuat di Hadapannya Tanpa Persetujuan Semua Ahli Waris Dalam RUPS - Ramadhan, Gilang; Lyanthi, Merline Eva (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
A transfer deed made before a notary is a guarantee of rights to shares. There are still many problems with transfer deeds being submitted to the court by the heirs of the share giver when the transfer is carried out without the knowledge of the other heirs. This is detrimental to the rights the heirs should receive. The validity of a conservation deed that is not guided by applicable regulations can result in the conservation deed becoming invalid. This research method is normative using a statutory and regulatory approach and a contextual approach. The results of the research in this study are that a transition is an agreement that must be guided by Article 1320 of the Civil Code regarding the conditions for the validity of an agreement, a transition in the case of not fulfilling all the elements of the agreement including agreement, skills, a certain thing and a lawful cause. This results in the deed of transfer being invalid. People who are no longer competent to carry out legal actions need forgiveness from their biological children and the purpose of all heirs because biological children also have rights to the object of preserving shares. The notary who makes the deed of transfer can be held responsible for his negligence which results in losses for heirs based on Article 1365 of the Civil Code. Responsibilities imposed on maintenance include professional responsibility, civil responsibility and administrative responsibility.